Effect Of Magnesium-Silicon Substitution On The Characteristics Of Carbonated Hydroxyapatite For Synthetic Bone - Zainudin, Harmiza (2018)
The nano-sized B-type magnesium-silicon carbonated hydroxyapatite (Mg-Si CHA) powders was successfully synthesized by nanoemulsion method through direct pouring (DP) technique at ambient temperature. Magnesium (Mg) and silicon (Si) were substituted into the carbonated hydroxyapatite (CHA) lattice structure in order to mimic the chemical composition of the human natural bone. The Mg-Si CHA particles exhibit angular or near spherical-like in shape with the dimension of 10-40 nm (length) and 5-20 nm (width). The incorporation of less than 1% of Mg and Si into the CHA lattice appears to have no direct effect on the phase composition, as evidenced by X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) results. Sintering was then performed on the Mg-Si CHA sample at 800°C and 2 hours soaking. During the cooling stage, the sintered sample was taken out from the furnace when the temperature reaches 200°C and placed in a desiccators. Wet carbon dioxide gas (CO2) was pumped into the desiccators to compensate the carbonate loss during sintering. The carbonate content of sintered Mg-Si CHA was 6.80%, which is fall in the range typically reported for natural bone (3 to 8%). In vitro bioactivity of the Mg-Si CHA was evaluated through immersion sample in simulated body fluid (SBF) solution as a medium and cytotoxicity test in term of cell culture response. The results revealed that the Mg-Si CHA had good bioactivity by rapid apatite formation ability and found to be non-cytotoxic on the human fibroblast, as demonstrated by high cell viabilities. In conclusion, Mg-Si CHA may be used as a synthetic bone substitution material.